Accounting for real estate transactions a guide for public accountants and corporate financial professionals - Davis, Maria K. (Wiley corporate F & A., 2012)
"Accounting for Real Estate Transactions, Second Edition is an up-to-date, comprehensive reference guide, specifically written to help professionals understand and apply the accounting rules relating to real estate transactions. This book provides financial professionals with a powerful tool to evaluate the accounting consequences of specific deals, enabling them to structure transactions with the accounting consequences in mind, and to account for them in accordance with US GAAP. Accountants and auditors are provided with major concepts, clear and concise explanations of real estate accounting rules, detailed applications of US GAAP, flowcharts, and exhaustive cross-references of the authoritative literature"--